Analisis Efektivitas Pengawasan BPK terhadap Pengelolaan Keuangan Daerah - Syahriful Ahyar; Kevin Immanuel Manurung; M. Nurdin; W Pangestoeti (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
This study analyzes the effectiveness of the Republic of Indonesia's Audit Board (BPK) in supervising regional financial management. The aim is to assess the extent to which BPK's supervision has encouraged the creation of good governance in regional financial management while identifying obstacles that hinder its effectiveness. Using qualitative methods and secondary data from existing documents and reports, the results of the study indicate that although BPK has attempted to improve accountability and transparency, there are still a number of significant challenges, including low compliance with recommendations and the influence of external factors. This study concludes with recommendations to strengthen BPK's capacity and improve coordination with related institutions to encourage better regional financial management.